Neck Circumference: A Novel Anthropometric Tool for Screening Obesity Among Young Adults - Mouna Hogalagere Sriramappa; Hamsa Lokanath; Jai Krishna Madarakkal Gunaseelan; Chittem Sravana Deepthi; Anu Priya Mathew Chirakkara; Tapasi Lahari Reddy (Medsci Publications, 2024)
Background: Obesity is a global health concern characterized by excessive fat accumulation, posing significant health risks that affect all age groups. Particularly among young adults, including medical students, obesity can lead to physical and psychosocial consequences, emphasizing the need for effective screening. The study was conducted to evaluate the effectiveness of using neck circumference as a screening tool for detecting obesity among young adults by assessing its correlation with other anthropometric measurements and determining the appropriate cut-off points Methodology: A cross-sectional study was conducted among 146 medical students at the Apollo Institute of Medical Sciences and Research, Chittoor, Andhra Pradesh. Data were collected using a semi-structured questionnaire and various anthropometric measurements, including neck circumference. Results: Neck circumference was higher among males, with a mean of 34.4±2.1cm for males and 30.2±1.9cm for females. Neck circumference showed significant positive correlations with height, weight, Body Mass Index, waist-hip ratio, hip and waist circumference. Neck circumference is proposed as a screening tool for assessing obesity among young adults, with cut-off values of 34cm for males and 30cm for females. Conclusions: Neck circumference is an effective screening tool for obesity among young adults, correlating with conventional anthropometric measures.